2001
DOI: 10.1161/01.cir.103.25.3123
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibition Attenuates Hypofibrinolysis and Reduces Cardiac Perivascular Fibrosis in Genetically Obese Diabetic Mice

Abstract: Thus, inhibition of proteo(fibrino)lysis and augmented tissue factor expression in the heart precede and may contribute to the coronary perivascular fibrosis seen with obesity and insulin resistance. Furthermore, inhibition of ACE activity can attenuate all 3 phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Altered characteristics of left ventricular capillaries in genetically obese diabetic rats have been reported (47). In a preliminary study, we also characterized capillary profiles in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 89%
“…Altered characteristics of left ventricular capillaries in genetically obese diabetic rats have been reported (47). In a preliminary study, we also characterized capillary profiles in fructose-fed rats.…”
Section: Discussionmentioning
confidence: 89%
“…30,31 An angiotensin-converting enzyme inhibitor decreased the inflammatory response in the myocardium of diabetic animals. 32 An ARB improved cardiac diastolic function and decreased fibrosis of diabetic rats. 33 In the present study, cardiac function was impaired in db/db mice, which is what was found in previous reports, 34,35 and candesartan treatment improved cardiac function.…”
Section: Discussionmentioning
confidence: 89%
“…This may point to fat storage/turnover capacity as the major process for long-term weight gain in men. In genetically obese diabetic mice, it was shown that ACE-inhibition blocks PAI-1 activity indicating that ACE is necessary for the formation of active PAI-1 (Zaman et al 2001). ACE converts angiotensin I into angiotensin II, and in humans, angiotensin II increases the expression of PAI-1, whereas inhibition of ACE decreases PAI-1 in plasma and tissues (Brown et al 1998(Brown et al , 1999.…”
Section: Discussionmentioning
confidence: 99%